Review of Ancistrus (Siluriformes: Loricariidae) from the northwestern Guiana Shield, Orinoco Andes, and adjacent basins with description of six new species - de Souza, Lesley S.; Taphorn, Donald C.; Armbruster, Jonathan W. (Zootaxa, 2019)
The Orinoco Andes and northwestern Guiana Shield (Essequibo, Orinoco, Branco, and upper Negro) were found to contain 11 species of Ancistrus, six of which are new. We additionally examine A. brevifilis from the Río Tuy of Venezuela and A. trinitatis from the island of Trinidad. The species in the region can be broken up into dorsoventrally flattened species (A. leoni new species, A. lithurgicus, and A. macropthalmus), white to yellow-dotted species (A. kellerae new species, A. nudiceps, and A. patronus new species), wide-jawed species (A. amaris new species and A. yutajae new species), and white-spotted species (A. brevifilis, A. leucostictus, A. trinitatis, A. saudades new species, and A. triradiatus). Distributions of Ancistrus support the Proto-Berbice hypothesis as A. saudades is found in the upper reaches of the Ventuari, Caura, and Caroni rivers, which were thought to have once flowed into the Proto-Berbice. In addition, although A. nudiceps does not appear to have split once the Takutu River was captured by the Branco, the progenitor of A. leucostictus and A. saudades did speciate with the populations on either side of the Rupununi Portal differing by 7% sequence divergence of the mitochondrial Cytochrome b gene. Besides the descriptions of the new species, we redescribe the others occurring in the area, and adjacent watersheds. We provide a key for their identification, and a preliminary hypothesis of relationships based on DNA sequences of the few species for which tissue samples are available.